1993
DOI: 10.3109/15563659309025762
|View full text |Cite
|
Sign up to set email alerts
|

The Basis of the Paradoxical Disturbance of Temperature Perception in Ciguatera Poisoning

Abstract: The basis of the paradoxical reversal of temperature perception commonly described in ciguatera poisoning has never been defined. The sensations experienced are described as tingling, burning, "dry ice-like", smarting, and "electric". Studies have demonstrated that these types of sensations are generated in C-polymodal nociceptor fibers in skin and deep structures and the intensity of these sensations depends on the intensity of discharge in these fibers. Ciguatoxin causes persistent sodium channel opening in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 15 publications
2
29
0
1
Order By: Relevance
“…Compounds such as gambierol are described to be produced by G. toxicus dinoflagellates, but relatively little is known about their targets. Although sodium and potassium channels have been proposed in the literature as possible targets (Inoue et al, 2003;Ghiaroni et al, 2005;Louzao et al, 2006), very few papers can couple these targets to the intoxication symptoms (Cameron, 1993). In this article, we define VGPCs as a physiological target of gambierol, examine its selectivity and speculate on gambierol's role in CFS intoxications.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds such as gambierol are described to be produced by G. toxicus dinoflagellates, but relatively little is known about their targets. Although sodium and potassium channels have been proposed in the literature as possible targets (Inoue et al, 2003;Ghiaroni et al, 2005;Louzao et al, 2006), very few papers can couple these targets to the intoxication symptoms (Cameron, 1993). In this article, we define VGPCs as a physiological target of gambierol, examine its selectivity and speculate on gambierol's role in CFS intoxications.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, because CTX-sensitive voltage-gated sodium channels have been found in all of the systems affected by CFP (i.e., brain, skeletal muscle, heart, peripheral nervous system, sensory neurons), these channels may mediate the symptomatology of CFP [121,122,123,124,125,126,127,128,129,130,131,132,133]. As an example, cold allodynia may be attributable to a CTX-induced modification of the voltage-gated sodium channels in A-delta and C fibers [134], which carry thermal and pain impulses through the spinal cord to the brain [135]. Of note, nerve conduction studies of patients with acute CFP reveal a disturbance in both sensory and motor conduction [101].…”
Section: Pathophysiology Of Cfpmentioning
confidence: 99%
“…Studies have shown that previous ciguatera patients experiencing temperature inversion, in a controlled environment, may do so as a result of increased nerve depolarisation in thinly myelinated Ad fibres and unmyelinated C fibres. 34 This observation could also explain the increased nociception. Although these findings go some way to explaining the neurological disturbances associated with ciguatera, it is still an area which is poorly understood.…”
Section: Discussion Epidemiology and Public Healthmentioning
confidence: 97%